2008
DOI: 10.2174/1874126600802010010
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Characterization of Behavior and the Predominant Species of Flavonoids in Physiological Buffer: Determination of Solubility, Lipophilicity and Anticancer Efficacy

Abstract: The objectives of this study were to investigate the behavior of flavonoids in an aqueous physiological buffer and to determine the structural and functional group substitution which is responsible for their anticancer action. The deprotonated anionic form of 7 flavonoids can easily be determined using spectrophotometry, and owing to its charged state, is highly soluble in aqueous physiological buffer and is not prone to aggregation. The protonated form of these 7 flavonoids is much less soluble and tends to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
(20 reference statements)
2
21
0
1
Order By: Relevance
“…These results show that colour can reflect, at least in part, the antioxidant activity of a honey sample, in agreement with the conclusions of Beretta and et al (2005) and Piljac-Žegarac and et al (2009). In the current study, it seemed that the flavonoids were mainly flavonolbased, as these do not absorb in the 500 -700 nm range (Tungjai et al, 2008). It is possible that other non-flavonoid polyphenolic constituents were also present in these honey samples.…”
supporting
confidence: 90%
“…These results show that colour can reflect, at least in part, the antioxidant activity of a honey sample, in agreement with the conclusions of Beretta and et al (2005) and Piljac-Žegarac and et al (2009). In the current study, it seemed that the flavonoids were mainly flavonolbased, as these do not absorb in the 500 -700 nm range (Tungjai et al, 2008). It is possible that other non-flavonoid polyphenolic constituents were also present in these honey samples.…”
supporting
confidence: 90%
“…2a and b). These signified that quercetin was ionized and should be presented in neutral and positive charge form (Tungjai et al, 2008). Similar results were obtained for quercetrin and rutin (Fig.…”
Section: Serum Albumin Protein Is Potential Carrier and Spontaneouslysupporting
confidence: 84%
“…Cell lines, cell culture and cytotoxicity assay: The human erythromyelogenous leukemic cell line (K562) and its DOX-resistant, P-glycoprotein-overexpressing K562/adr subline, (Choiprasert et al, 2010;Tungjai et al, 2008;Dechsupa and Mankhetkorn, 2009;Ayudhya and Mankhetkorn, 2009;Garnier-Suillerot et al, 2001) and the human small cell lung carcinoma cell line (GLC4) and its DOX-resistant, MRP1-overexpressing GLC4/adr subline (Choiprasert et al, 2010;Tungjai et al, 2008) were routinely cultured in RPMI 1640 medium supplemented with 10% (v/v) fetal calf serum in a humidified atmosphere with 5% CO 2 at 37°C. For the cytotoxicity assays, cells were plated at a density of 5×10 5 cell.mL ) so that cells were in exponential growth phase.…”
Section: Quercetinmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that, beside their efficient antioxidant activity, quercetin, apigenin, kaempferol and eriodyctiol also efficiently inhibited cell growth of various cancer cell types including breast cancer MDA-MB 435, erythromyelogenous leukemic K562, small cell lung carcinoma GLC4 cells (Suttana, 2009). The particular interests are these flavonoids mediated almost the same antiproliferation efficacy in multidrug-resistant cancer cells such as K562/adr which over-expressed P-glycoprotein and GLC4/adr which over-expressed MRP1 protein when compared with their corresponding drug-sensitive cells (Tungjai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%